Vamping and family dynamics in teenagers - Quevedo Moreira, Michelle Elizabeth; Chiliquinga Véjar, Lorena del Carmen (SATHIRI, 2022)
This research is based on the study of the problem generated by the excessive use of cell phones at night, known as vamping, which produces alterations associated with insomnia and other health effects. The study aims to determine the incidence of this practice in the family dynamics of adolescents. The methodology used was quantitative in nature with an exploratory, descriptive and correlational scope, the study group was made up of 171 adolescents, for the survey three instruments were used: mobile phone dependency test, Oviedo sleep questionnaire, and the sleep perception questionnaire. Family Functioning. The results found determined the incidence of vamping in the family dynamics of adolescents, the statistical test of the Kruskal-Wallis Test also demonstrated the presence of a positive correlation. On the other hand, it was determined that cell phone dependence and sleep quality are associated with the type of family, where the problems are accentuated in severely dysfunctional families and are reduced as functionality within the home improves.
Keywords: Family; Information technology; mobile phone addiction; teenagers